1977
DOI: 10.1161/01.res.41.5.702
|View full text |Cite
|
Sign up to set email alerts
|

The myocardial cell surface, its histochemistry, and the effect of sialic acid and calcium removal on its stucture and cellular ionic exchange.

Abstract: SUMMARY The surface of neonatal rat cells in culture, neonatal rat hearts, and adult rabbit hearts have qualitatively similar responses to lanthanum, ruthenium red, and colloidal iron stains. All demonstrate a surface coat and external lamina with abundant negatively charged sites. Cells with intact surface structure do not permit entry of lanthanum (La 3+ ) intracellularly. The surface of all the myocardial cells studied contained abundant sialic acid distributed in two distinct layers, one in the surface coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
87
1

Year Published

1978
1978
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(95 citation statements)
references
References 42 publications
7
87
1
Order By: Relevance
“…It remains uncertain as to whether the major portion of Ca involved in E-C coupling moves across the sarcolemma with each beat or whether a portion is released from internal sarcotubular sites by the mechanism of Ca-induced Ca release (21 plex (22). This complex contains large amounts of glycoprotein and glycolipid and carries a large quantity of negatively charged sites which are believed to represent the loci for Ca binding.…”
Section: Model For Myocardial Contractile Controlmentioning
confidence: 99%
“…It remains uncertain as to whether the major portion of Ca involved in E-C coupling moves across the sarcolemma with each beat or whether a portion is released from internal sarcotubular sites by the mechanism of Ca-induced Ca release (21 plex (22). This complex contains large amounts of glycoprotein and glycolipid and carries a large quantity of negatively charged sites which are believed to represent the loci for Ca binding.…”
Section: Model For Myocardial Contractile Controlmentioning
confidence: 99%
“…Langer and his co-workers have found that removal of sialic acid from cultured myocardial cell surface by treatment with neuraminidase produces an enhancement of the Ca2" permeability of the membrane (Frank et al, 1977;Langer et al, 1979;. This observation suggested that the glycocalyx might in some way regulate the calcium ions which participate in the contractile response.…”
Section: Introductionmentioning
confidence: 98%
“…Coronary perfusion with a calcium-free solution results in the development of an electromechanical dissociation (Mines, 1913), but may in addition lead to an increase of the sarcolemmal permeability to calcium (Frank et al, 1977). As a consequence, reperfusion of the heart with calcium-containing solution results in a massive influx of calcium into the cells, followed by exhaustion of tissue high-energy phosphates, the rapid onset ol myocardial contracture, massive release of cell constituents, and extensive uItrastructural damage (Zimmerman et al , 1967;Boink et al, 1976;Hearse et al , 1978).…”
Section: Introductionmentioning
confidence: 99%